VD_FINDINFO Jug / 2011 / 52 vom 6. April 2011 - VD Tribunal cantonal (2011)
DIVORCE, PRÉVOYANCE PROFESSIONNELLE, PARTAGESENS GÉNÉRAL | 142 al. 2 CC, 22 LFLP, 25a al. 1 LFLP, 15 LPP, 7 OLP, 8a OLP, 12 OPP2